2023
DOI: 10.3390/molecules28155928
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PCSK9 Inhibition on the Stabilization of Atherosclerotic Plaque Determined by Biochemical and Diagnostic Imaging Methods

Marcin Basiak,
Marcin Hachula,
Michal Kosowski
et al.

Abstract: Atherosclerosis is a multifactorial, progressive, chronic inflammatory disease. Ultrasound and magnetic resonance imaging are the most accurate predictors of atherosclerotic plaque instability (MRI). Cytokines such as osteopontin, osteoprotegerin, and metalloproteinase 9 could be used as the most recent markers to identify and track the efficacy of anti-atherosclerotic therapy. Patients with USG and MRI-verified unstable atherosclerotic plaque were included in the study. Biomarker concentrations were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Our study provides a novel anti-atherosclerotic mechanism of bosentan regarding its anti-inflammatory effects. We and other investigators have demonstrated the strong contribution of inflammation to atherosclerosis vulnerability [8,39,40]. We also noticed a complementary pattern after bosentan and atorvastatin in the modulation of inflammatory mediators, focusing on TNF-a and MCP-1.…”
Section: Discussionsupporting
confidence: 76%
“…Our study provides a novel anti-atherosclerotic mechanism of bosentan regarding its anti-inflammatory effects. We and other investigators have demonstrated the strong contribution of inflammation to atherosclerosis vulnerability [8,39,40]. We also noticed a complementary pattern after bosentan and atorvastatin in the modulation of inflammatory mediators, focusing on TNF-a and MCP-1.…”
Section: Discussionsupporting
confidence: 76%
“…We examined the expression of select MMPs and TIMPs, and found that MMP9 and MMP12 were upregulated in atherosclerotic aortas from Acod1 –/– mice versus WT, at both mRNA and protein levels ( Supplemental Figure 3 , A and B). These MMPs have been found to promote plaque instability and increase atherosclerotic burden ( 22 , 23 ), consistent with more severe atherogenesis in Acod1 –/– versus WT mice.…”
Section: Resultsmentioning
confidence: 71%
“…Beyond the LDL cholesterol regulation, PCSK9 has been shown to have multiple roles in vascular diseases ( 7–10 ), PCSK9 inhibitors exhibit anti-inflammatory properties, contribute to the stabilization of atherosclerotic plaques ( 9 ), and reduce infarction volume, as seen in in-vitro and animal studies ( 11 , 12 ). These pleiotropic effects of PCSK9 inhibitors have also observed in small human studies ( 11 , 13 ), with follow-up studies using IVUS showing regression of atherosclerotic plaques ( 14 ). Based on these insights, several recent and ongoing studies have been employing PCSK9 inhibitors early in the treatment process and off-label for patients with acute myocardial infarction who are receiving percutaneous coronary intervention ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 61%